2008
DOI: 10.1007/s11829-008-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Flower colour variation across a hybrid zone in Antirrhinum as perceived by bumblebee pollinators

Abstract: To assess if pollinators' behaviour could explain the maintenance of hybrid zones between different flower colour morphs, we analyzed flower colour variation in an Antirrhinum hybrid zone using spectrometry and a model of bee perception. Some colours generated by hybridization were not observed in any Antirrhinum species and even appeared to be rare among angiosperms. Variation in flower colours within the hybrid zone was continuous; the most similar colours were predicted not to be discriminated from one anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Previous work suggested that the genus Antirrhinum conformed to this trend and that species boundaries were maintained almost exclusively with pre‐zygotic barriers (Schwarz‐Sommer et al ., ; Langlade et al ., ; Whibley et al ., ; Feng et al ., ). Specifically, in Antirrhinum , the importance of geographical isolation has been strongly emphasized (Rothmaler, ; Webb, ; Vargas et al ., ) and the influence of pollinators on interspecific gene flow limitation has also been suggested as an important barrier (Whibley et al ., ; Tastard et al ., ; Shang et al ., ; Suchet et al ., ), although there are few studies on this barrier under cultivation conditions and it is highly overlooked in the natural environment. Unlike pre‐zygotic barriers, post‐zygotic isolation in Antirrhinum has been considered to be weak (Baur, ; Hackbarth et al ., ; Rothmaler, ; Rieger, ; Stubbe, ; Andalo et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work suggested that the genus Antirrhinum conformed to this trend and that species boundaries were maintained almost exclusively with pre‐zygotic barriers (Schwarz‐Sommer et al ., ; Langlade et al ., ; Whibley et al ., ; Feng et al ., ). Specifically, in Antirrhinum , the importance of geographical isolation has been strongly emphasized (Rothmaler, ; Webb, ; Vargas et al ., ) and the influence of pollinators on interspecific gene flow limitation has also been suggested as an important barrier (Whibley et al ., ; Tastard et al ., ; Shang et al ., ; Suchet et al ., ), although there are few studies on this barrier under cultivation conditions and it is highly overlooked in the natural environment. Unlike pre‐zygotic barriers, post‐zygotic isolation in Antirrhinum has been considered to be weak (Baur, ; Hackbarth et al ., ; Rothmaler, ; Rieger, ; Stubbe, ; Andalo et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, discriminant function and cluster analyses can be used to investigate how distinctive a group of individuals is compared to other individuals (Ajuria Ibarra & Reader, ; Feeney et al , ). One should keep in mind, however, that statistically significant clusters may not be distinguished by a perceiver and thus can be visually irrelevant (Tastard et al , ). In some cases, geographical data may also be necessary to interpret the value of colour clusters correctly.…”
Section: Colour Diversitymentioning
confidence: 99%
“…Flower colour is under selection by pollinators (Kevan and Baker 1983;Rodriguez-Girones and Santamaria 2004;Tastard et al 2008;Waser 1983;Whibley et al 2006). There are indeed several studies associating shifts in flower colours with shifts in pollinator type (Altshuler 2003;Bradshaw and Schemske 2003).…”
Section: Introductionmentioning
confidence: 99%